Guide to mathematical modelling - Edwards, Dilwyn (Palgrave, 2001)
A basic introduction to Mathematical Modelling, this book encourages the reader to participate in the investigation of a wide variety of modelling examples. These are carefully paced so that readers can identify and develop the skills which are required for successful modelling.